SURGICAL SITE INFECTION RELATED RISK FACTORS AND USAGE OF ANTIBIOTICS IN TWO DIFFERENT TERTIARY CARE HOSPITALS OF DHAKA CITY, BANGLADESH - Monjur, Forhad; Rizwan, Farhana; Ghosh, Nobo Krishna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Surgical site infection (SSI) is the most common complications following surgical procedures. The aim of the study was to assess the risk factors for SSI and the antibiotic treatment pattern following post-operative infection. Methods: This retrospective study has been considered the data of 156 surgical patients from two tertiary care hospitals in Dhaka city of Bangladesh. Result: The majority (31.4%) of the surgical patients came from the age group 40 to 49 years. A total of 8 SSI cases were discovered, 5 cases (8.9%) from Hospital-1, which was relatively higher (3%) than Hospital-2. Wound class contaminatedâ€ was found in 6 cases, and the ratio is almost 1:3 or 75%. The duration of surgery within 90â€“120 min for 50% of SSI patients (4/8). Most frequent types of surgery were colorectal surgery (56.4%, 88/156), followed by various grades of fistula (24.4%, 38/156). The prophylaxis antibiotic was ceftriaxone, used by 77 (49.4%) cases. Commonly used antibiotic was ciprofloxacin, administered in 33 (21.2%) patients as a single therapy. Third-generation cephalosporins (cefixime, ceftriaxone, and cefuroxime) were found at the drug of choice in combination with gentamicin/metronidazole/nitazoxanide or amikacin. Conclusion: This study tried to give a little overview of SSI in different hospital settings, whereas improvement of preventive measures, early detection, and management of SSI is the main concern of nowadays. Further research should be done to get the detail by considering all the relevant factors of SSI.